Assédio sexual nas academias de ginástica de Iguatu-CE: percepção de mulheres praticantes de musculação - Pinheiro, Maria Rosângela Dias (2020)
Harassment has been an object of great relevance in contemporary times, awakening reflections in more diverse areas of the scientific academic and social world. The work aimed to investigate how women bodybuilders perceived the harassed in gyms in Iguatu-CE. Characterized as a qualitative field and descriptive research. Participated in the study of twenty-five women bodybuilders in the gyms in Iguatu-CE. Two instruments were applied: the structured questionnaire with open and closed questions, aiming to characterize the sociodemographic profile seeking information related to the economic and social aspects of the study participants, the frequency of activities at the gym and the reasons for seeking to practice weight training; and the semi-structured interview with a script of subjective questions prepared by the researcher, in order to obtain information from the study's narrators about the perception of sexual harassment and the impact of this experience on her life and on the regular practice of physical activities. The characterization of the participants was presented descriptively, and the narratives were transcribed and analyzed using the content analysis method and exposed through diagrams, revealing a series of categories and subcategories. The research is presented in the form of two articles: in the first, the narratives of women who practice weight training on sexual harassment are analyzed; and, in the second, the impact of sexual harassment experiences in relation to daily life and the regular practice of physical activities by women practicing weight training is characterized. We concluded that sexual harassment is an act that violates sexual freedom, invades privacy without the consent of the other person, in addition to ulterior motives, causing embarrassment in the harassed person. Sexual harassment is related to sexual design characterized by mean comments and obscene gestures, jokes, touches, inconvenient compliments related to body parts. As for the impacts of sexual harassment, these had a negative influence on the life and regular practice of physical activities by bodybuilders women on moral and psychological aspects. The moral impacts refer to those suffered constraints, so they move away from the bodybuilding because they feel vulnerable face the experienced circumstances, avoiding contact to protect themselves from episodes of harassment. The psychological impacts correspond to the lack of motivation to attend the gym space; nuisance and discomfort faced with the phenomenon; fear of returning to activities for fear of suffering the experience again; panic perform exercises under the eyes of men; and the search for psychological help to overcome traumas.